2017
DOI: 10.1007/s12070-017-1188-0
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Noise-Induced Hearing Loss (NIHL) and its Symptomatic Correlation with Audiometry Observations in Type II Diabetes

Abstract: Type II diabetic mellitus (DM) is a chronic metabolic disease that impairs normal insulin production and glucose transport to the liver and muscles. In the India, about 1-5% population suffer from diabetes or related complication. So there is need to cure this disease. DM chronic auditory complications may include spiral ganglia atrophy, degeneration of the vestibulocochlear nerve myelin sheath, reduction of the number of spiral lamina nerve fibres, and thickening of the capillary walls of the stria vascularis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The hearing loss in most of DM patients may not be due to noise exposure and high frequency sensori-neural hearing loss is predominant. [6][7][8] Some studies demonstrated that diabetes effects on hearing are more frequent among patients younger than 50 years old [9][10][11]. So endocrinologists need to control hearing in DM patients, in addition to other common diabetic complications.…”
Section: Introductionmentioning
confidence: 99%
“…The hearing loss in most of DM patients may not be due to noise exposure and high frequency sensori-neural hearing loss is predominant. [6][7][8] Some studies demonstrated that diabetes effects on hearing are more frequent among patients younger than 50 years old [9][10][11]. So endocrinologists need to control hearing in DM patients, in addition to other common diabetic complications.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of hazardous noise in the workplace potentially results in individuals acquiring a disabling hearing loss, marked by hearing thresholds below 40 dBs (Yadav et al 2015). Disabling hearing loss is the 'most prevalent, least recognised and least understood physical disability' (Dugan 2003, p. 9) and is a major contributor to the global burden of disease for individuals, families, communities and countries (Copley & Frederichs 2010;Hermanus 2007).…”
Section: Occupational Noise-induced Hearing Loss In the Mining And Mi...mentioning
confidence: 99%
“…asserted that NIHL is influenced by health conditions and illnesses such as HIV, AIDS and TB. Other authors have investigated the link between NIHL and blood pressure and hypertension Liu et al 2016;Wang et al 2018), cardiovascular disease Li et al 2019;Xua & Francis 2019) and diabetes (Ashkezari et al 2018;Soares et al 2018;Yadav & Yadav 2018). Furthermore, individuals without a history of hearing loss may acquire hearing loss because of the ototoxic nature of the drug regimen used to treat HIV, AIDS and TB (Khoza-Shangase 2020a).…”
Section: Quaternary Preventionmentioning
confidence: 99%